1997
DOI: 10.1128/jcm.35.11.2883-2885.1997
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Bartonella henselae infection and correlation with disease status in cats in Switzerland

Abstract: The prevalence of infection with Bartonella henselae was investigated in cats from different areas of Switzerland. Serum samples of 728 cats were examined for antibodies to B. henselae by immunofluorescent antibody testing, and the results were analyzed with a view to a possible correlation between a positive titer and signalment, clinical signs, infection with feline leukemia virus (FeLV), feline immunodeficiency virus (FIV), feline coronavirus (FCoV), or feline spumavirus (FeSFV), and the living environments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
59
1
11

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 21 publications
8
59
1
11
Order By: Relevance
“…Detectable antibodies to Bartonella spp. were found in 61% of the cats, a prevalence similar to those reported in other studies (3.7-81%) [8,[29][30][31]. The antibody response to B. henselae has been demonstrated to occur 2 weeks after infectious challenge [32].…”
Section: Discussionsupporting
confidence: 86%
“…Detectable antibodies to Bartonella spp. were found in 61% of the cats, a prevalence similar to those reported in other studies (3.7-81%) [8,[29][30][31]. The antibody response to B. henselae has been demonstrated to occur 2 weeks after infectious challenge [32].…”
Section: Discussionsupporting
confidence: 86%
“…Antibodies against FIV and T. gondii were detected in several cats, as has been previously reported, which might have played a role in development of hyperglobulinemia. 21,22,33,38 In this study, all but one of the Bartonella spp. seropositive cats studied had polyclonal gammopathies.…”
Section: Discussionmentioning
confidence: 67%
“…bacteremia for gingivostomatitis and hepatic disease in cats. [19][20][21][22][23][24] Experimentally infected cats have been shown to have infiltrates of lymphocytes and plasma cells in a number of tissues, including the feline liver, pancreas, and kidneys. 15,18 Because serum biochemical panel results were not reported in those studies, it remains unknown whether these inflammatory infiltrates were associated with laboratory evidence of disease.…”
mentioning
confidence: 99%
“…In some studies, B. henselae seropositivity rate has not been gender related (Glaus et al, 1997;Maruyama et al, 2003). Maruyama et al (1998) and Bergmans et al (1997) found that male cats had higher positives, whilst Sander et al (1997) found that female cats had higher positives.…”
Section: Discussionmentioning
confidence: 99%